The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/app.48243
|View full text |Cite
|
Sign up to set email alerts
|

Promoted dispersion of silica and interfacial strength in rubber/silica composites by grafting with oniums

Abstract: The dispersion of filler and interfacial interaction are crucial in determining the properties of rubber composites. Aiming to improve the dispersion and filler-rubber interaction, we introduce rubber graft bearing oniums in a rubber/silica composite. To fulfill this goal, the graft, which is prepared via thio-ene click reaction between 1-methylimidazolium mercaptopropionate (MMP) and the pendent vinyl groups of a solution-polymerized styrene-butadiene rubber (SSBR), is introduced into the silica-filled styren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…24 At the same time, the loss peak area can indicate the interaction between fillers. 8,25 The peak area shows a decreasing trend with strength of the interaction between rubber and filler. The dependences of tan δ on temperature for the NR-DESx are shown in Figure 3(a).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…24 At the same time, the loss peak area can indicate the interaction between fillers. 8,25 The peak area shows a decreasing trend with strength of the interaction between rubber and filler. The dependences of tan δ on temperature for the NR-DESx are shown in Figure 3(a).…”
Section: Resultsmentioning
confidence: 98%
“…Ionic liquids have also attracted people’s attention due to their good physical and chemical properties. 68 Du et al 9 studied the effect of a kind of ionic liquid, 1-butyl-3-methylimidazoliumtetrafluoroborate (BMI), on the properties of silica reinforced styrene-butadiene rubber (SBR). The results show that the ionic liquid can effectively improve the dispersion of silica in SBR, and can also improve the mechanical properties, wear resistance of the composites, the rolling resistance, and wet skid resistance of SBR.…”
Section: Introductionmentioning
confidence: 99%
“…A silane coupling agent is confirmed to be capable of improving the dispersion of silica in rubber significantly, but the need of additional high-temperature treatment increases the complexity of processing [30]. It has been very recently demonstrated that intra-chain functional groups in rubber can effectively improve the dispersion of silica through polar interaction or chemical connection [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [14] developed surface modified silica nanoparticles by combining noncovalent and covalent modification processes in a simple, efficient and costeffective method. Weng et al [15] developed a new way to promote the dispersion of silica and interfacial strength in rubber/silica composites by grafting with oniums. Liu et al [16] established a simple inhibition-grafting method to prepare silica/polydimethylsiloxane nanocomposites with superior mechanical properties and a low viscosity.…”
Section: Introductionmentioning
confidence: 99%